METHODOLOGICAL FOUNDATIONS OF TRAINING AGRICULTURAL ENGINEERS FOR THE IMPLEMENTATION OF ALTERNATIVE FUELS: FROM COMBUSTION THEORY TO THERMAL EFFICIENCY - Pukas, Vitalii; Govorov, Oleksandr; Volynkin, Mykola; Pecheniuk, Andrii (Public Management and Policy, 2026)
The article reveals the conceptual foundations of forming the professional profile of a modern agricultural engineer in the context of the global transformation of the agricultural energy sector. The authors substantiate the necessity of transitioning from a traditional educational model to an innovative methodology, where fundamental knowledge of combustion theory serves as the basis for achieving maximum thermal efficiency of technical systems. The publication provides a detailed analysis of the cause-and-effect chain between the physicochemical specifics of alternative energy sources and the dynamics of in-cylinder processes. It considers a methodological approach that enables future specialists to master the tools for adapting engines to operate on oxygenated fuel compositions through mathematical modeling and experimental research. Particular attention is paid to the algorithmization of practical training in laboratories. The authors describe the logic of a student's actions during bench tests as a process of consistently seeking a compromise between power, fuel economy, and environmental safety. The article proves that an engineer's “green” competence is formed not as an abstract ideology, but as the ability to manage the emission of toxic components through the precise adjustment of fuel supply parameters. The methodological novelty of the work lies in the proposed structure of educational modules, where theoretical content is integrated into practice-oriented case studies. The conditions for creating an interactive educational environment are described, which require specific material and technical equipment to visualize complex thermodynamic phenomena. In conclusion, the authors emphasize that the proposed methodology allows for the training of personnel capable not only of operating multi-fuel systems but also of initiating the implementation of renewable energy at the level of agricultural enterprises.